Improvement of lipid profile and hepatic oxidative stress in high-fat-diet- induced hyperlipidemic Swiss albino rats by Piper betle juice: evidences from in vivo and in silico studies - Jing, XiBo; Sarker, Md. Moklesur Rahman; Gifari, Md. Abu Jar; Maruf, Md. Rifat Alam; Alam, Safaet; Khan, Farzana; Soma, Mahfuza Afroz; Hossain, Md Sanower; Ming, Long Chiau; Ahmad, Shihab Uddin; Hasan, Raquibul (Cellular and Molecular Biology Association, 2022)
Piper betle L. leaves are very popular and traditionally used to chew with betel nut in many Asian countries. In this study, P. betle leaves juice (PBJ) was subjected to evaluation for its antihyperlipidemic activity in the high-fat-diet-induced hyperlipidemic rats model. Swiss albino rats were allowed to high-fat- diet for one month, followed by concurrent administration of PBJ for another month. The rats were then sacrificed and collected blood, tissues and organs. Pharmacokinetic, toxicological studies and molecular docking studies were performed using SwissADME, admetSAR and schrodinger suit-2017. Our investigation showed a promising effect of PBJ on body weight, lipid profile, oxidative and antioxidative enzymes, and the principle enzyme responsible for the synthesis of cholesterol. PBJ at 0.5 - 3.0 mL/rat significantly reduced body weight of hyperlipidemic rats compared to control. PBJ at the doses of 1.0, 1.5, 2.0, and 3.0 mL/rat significantly (p<0.05, p<0.01, p<0.001) improved the levels of TC, LDL-c, TG, HDL-c and VLDL-c. Similarly, PBJ doses starting from 1.0 mL/rat to 3.0 mL/rat reduced the oxidative biomarkers AST, ALT, ALP, and creatinine. The level of HMG-CoA was significantly reduced by PBJ doses 1.5, 2, and 3 ml/rat. A number of compounds have been found to have good pharmacokinetic profile and safety and 4-coumaroylquinic acid exerted the best docking score among them. Thus our findings clearly demonstrated the potential lipid-lowering activities of PBJ both in vivo and in silico studies. PBJ can be a good candidate for the development of antihyperlipidemic medication or as an alternative medicine.